2016
DOI: 10.1002/ardp.201500468
|View full text |Cite
|
Sign up to set email alerts
|

Quinoxaline‐Based Scaffolds Targeting Tyrosine Kinases and Their Potential Anticancer Activity

Abstract: Quinoxaline derivatives, also called benzopyrazines, are an important class of heterocyclic compounds. Quinoxalines have drawn great attention due to their wide spectrum of biological activities. They are considered as an important basis for anticancer drugs due to their potential activity as protein kinase inhibitors. In this review, we focus on the chemistry of the quinoxaline derivatives, the strategies for their synthesis, their potential activities against various tyrosine kinases, and on the structure-ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(30 citation statements)
references
References 106 publications
0
30
0
Order By: Relevance
“…In 2014, Shahin et al [13] designed a series of new quinoxaline-based scaffolds bearing amide, sulphonamide and urea moieties which were biologically evaluated for their inhibitory activity against VEGFR-2. In that study, compound 3 (Figure 1) displayed the best IC 50 value of 10.27 µM, while compound 4 (Figure 2) displayed the best inhibition percentage against VEGFR-2 which was 69% [6]. Furthermore, quinoxaline 5 having an amide group (Figure 2) has been also reported by Ramurthy et al as a potent Rapidly Accelerated Fibrosarcoma (Raf) kinase inhibitor [14].…”
Section: Introductionmentioning
confidence: 79%
See 1 more Smart Citation
“…In 2014, Shahin et al [13] designed a series of new quinoxaline-based scaffolds bearing amide, sulphonamide and urea moieties which were biologically evaluated for their inhibitory activity against VEGFR-2. In that study, compound 3 (Figure 1) displayed the best IC 50 value of 10.27 µM, while compound 4 (Figure 2) displayed the best inhibition percentage against VEGFR-2 which was 69% [6]. Furthermore, quinoxaline 5 having an amide group (Figure 2) has been also reported by Ramurthy et al as a potent Rapidly Accelerated Fibrosarcoma (Raf) kinase inhibitor [14].…”
Section: Introductionmentioning
confidence: 79%
“…Human protein tyrosine kinases (PTKs) play a central role in human carcinogenesis [3], whereas cell cycle progression, cell division and proliferation are viewed as a sequence of events controlled by a cascade of those protein kinases, so PTKs have emerged as promising new cancer therapy targets [4]. Quinoxalines are considered as an important basis for anti-cancer drugs as they are proved to be selective adenosine triphosphate (ATP) competitive inhibitors in many kinases [5] for example: vascular endothelial growth factor receptor (VEGFR), platelet-derived growth factor receptor (PDGFR), proto-oncogene non-receptor tyrosine-protein kinase (Src), c-Met proto-oncogene (c-Met kinase), epidermal growth factor receptor\human epidermal growth factor receptor (EGFR/HER-2), Janus kinase receptor (JAK-2), FMs-related tyrosine kinase 3 (FLT-3) and cyclin dependent kinase (CDK1,2,4,6) [6]. In 2016, Zghaib et al reported that imidazo[1,2- a ]quinoxaline derivatives were major microtubule-interfering agents with potent anticancer activity [7].…”
Section: Introductionmentioning
confidence: 99%
“…Quinoxaline and its derivatives exhibit diverse biological activities, such as anticancer, antibacterial, antiviral, anti-inflammatory [4][5][6]. Tetrazanbigen (TNBG) was a creatively designed and synthesized leading compound bearing the quinoxaline core and showing anticancer activity [7].…”
Section: Commentmentioning
confidence: 99%
“…The online‐only publication allows the inclusion of colored graphics and also other file formats without additional costs for the authors. Several topical review articles have been published, covering heterogeneous topics like epigenetics in cancer , heterocyclic tyrosine kinase inhibitors , biomarkers , beta‐cell regulators , privileged scaffolds , alternative antibiotics , antimycobacterial metabolites or enzyme‐oriented antimycotics , covalent inhibitors , heterologous antibiotic production as well as tool boxes or PPP models in drug discovery , not to mention the numerous excellent original papers. Therefore, I would like to thank all authors for their valuable contributions and all reviewers for their careful and most helpful support.…”
Section: Dear Colleaguesmentioning
confidence: 99%